2016
DOI: 10.1007/s00595-016-1349-x
|View full text |Cite
|
Sign up to set email alerts
|

Tumescent TAPP: laparoscopic inguinal hernia repair after the preperitoneal tumescent injection of diluted lidocaine and epinephrine saline solution and carbon dioxide gas

Abstract: PurposeLaparoscopic transabdominal preperitoneal inguinal hernia repair (TAPP) is technically difficult and not infrequently followed by postoperative complications and pain, especially when performed by inexperienced surgeons. To simplify TAPP and reduce postoperative pain, we devised a novel procedure whereby TAPP is carried out after the inguinal preperitoneal infiltration of diluted lidocaine and epinephrine saline solution and carbon dioxide gas (tumescent TAPP). This report introduces the concept of tume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Overall, 39 reports were found to be relevant to the research question. Of these, 3 were randomized controlled trials [11], [12], [13], 5 were prospective studies [14], [15], [16], [17], [18], 4 were case reports [10], [19], [20], [21], 25 were retrospective (registry) studies [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], and 2 were meta-analyses [47], [48].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 39 reports were found to be relevant to the research question. Of these, 3 were randomized controlled trials [11], [12], [13], 5 were prospective studies [14], [15], [16], [17], [18], 4 were case reports [10], [19], [20], [21], 25 were retrospective (registry) studies [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], and 2 were meta-analyses [47], [48].…”
Section: Methodsmentioning
confidence: 99%
“…Risk factors were identified. In addition, incidence rates were analyzed for various types of complications in 17 of the studies [11], [13], [15], [16], [18], [19], [20], [22], [24], [26], [29], [32], [36], [37], [38], [44]; if possible, the complications reported in the included studies were graded with regard to the Clavien-Dindo classification. Not all complications summarized here were reported in all of the studies.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19][20][21] a Pubmed search (keywords: "tumescent local anesthesia" and "inguinal hernia"). [4][5][6] Our study included the largest number of patients to date and showed the effectiveness of TLA in short-and long-term outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…TLA is utilized in other surgical areas; however, an appliance with inguinal hernia repair is not broadly performed. Only three English literature reports were uncovered with a Pubmed search (keywords: “tumescent local anesthesia” and “inguinal hernia”) 4–6 . Our study included the largest number of patients to date and showed the effectiveness of TLA in short‐ and long‐term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…RS and TAP blocks previously required percutaneous puncture, which carries a risk of introducing infection, causing bleeding, or damaging local structures. Recently, a percutaneous tumescent approach with diluted lidocaine and epinephrine was reported for preperitoneal dissection and local anesthesia under laparoscopic visualization . Laparoscopic visualization helps to determine anatomical structure and avoid causing damage.…”
Section: Discussionmentioning
confidence: 99%